A Review of Anti – Diarrheal Activity of Aegle marmelos - Rakulini, R.; Sounthararajan, K. (Journal of Complementary and Alternative Medical Research, 2019)
The aim of this study was review the anti – diarrheal activity of Aegle marmelos. Siddha literatures were obtained from the library of Unit of Siddha Medicine, University of Jaffna. Data was collected from books and internet and tabulated for the analysis. Beal Fruit Tree (Aegle marmelos) (Tamil name Vilvam, Kuvilam, Sinhala name Belli), belongs to the family of Rutaceae. It is the most valuable medicinal plant in Siddha system of Medicine due to its various medicinal properties. It is a small or medium sized deciduous tree. It has alternate leave arrangement, Its flowers are greenish white, Fruit globose, grey or yellowish colour, Seeds Numerous. Found all over the Sri Lanka. Fruit (both unripe & ripe), root – bark, leaves, rind of the ripe fruit & flowers are used in drug preparations. Un-ripe fruit is astringent, digestive & stomachic & a little constipative. According to Siddha, Aegle marmelos has bitter, astringent taste, hot potency, pungent bio availability and reduce Vatha, Pitha and Kapha dosha. Diarrhoeal diseases are amongst the most common infectious diseases worldwide resulting in 3.2% of all deaths killing about 1.8 million people globally each year. It is quite evident from this review that Aegle marmelos is an important medicinal herb and extensively used in Ayurveda, Siddha, unani and traditional medicine. Historically, Aegle marmelos has been used for the number of ethonobotanical purposes. The collected information suggests that Aegle marmelos has anti-diarrheal activity.
Keywords: Aegle marmelos; Antidiarrheal activity; Unripe fruit; Beal; Siddha